LDPE DEGRADING ABILITY OF RIEMERELLA STRAIN ISOLATED FROM THE GARBAGE DUMPING SITES OF VISAKHAPATNAM, INDIA - Bandi, Sai Spandana; Veluru, Sridevi; Mallisetty, Rishi; Talib Hamzah, Husam; Rao Poiba, Venkata; R., Srikanth (International Journal of Research -GRANTHAALAYAH, 2022)
Polyethylene is found to accumulate in the environment, posing a major ecological threat. Affordable and environmentally friendly treatments are need of the hour to combat this plastic pollution. A study was made to isolate microorganisms from a sample of garden soil and evaluate their degrading potential. The plastic sample tested in this study were Low Density Polyethylene shopping carry bag. The growth of LDPE degrading strains was carried out in Mineral salt agar medium with LDPE as the sole carbon and energy source. Six strains were isolated. One of the strains namely A3 was found to show maximum growth rate. It was known that LDPE is resilient to biodegradation. Nevertheless, the present work shows the utilization of LDPE by A3 strain as carbon source and indicates that microbes are familiarizing towards hydrocarbons. The phenotypic fingerprint like Gen III biolog was used to actuate the substrate utilization of strain A3 and identified it as, Riemerella anatipestifer. Preliminary growth studies were carried out initially. The optimal conditions were found to be pH of 7.1, temperature of 37ᵒC, contact time of 72hrs, LDPE weight of 0.042g and inoculums volume of 3v/v. LDPE degradation was confirmed by the weight loss which was found to be 20.09% after an incubation of 35 days. As per our work we found that, garden soil is a good source of bacteria that can degrade LDPE. These results also signify the potential of novel strain Riemerella Sp. to degrade LDPE films. This manuscript will pave the way for future studies on biodegradation.